Overview Hubungan Industrial : Study Case Penyelesaian Konflik Kerja Pada PT Swakarya Indah Busana Tanjungpinang. - Topo Yudhoyono Harsyahputra; Salsabila, Lubna (Prodi Ilmu Administrasi Negara, 2024)
The aim of this research is to analyze dispute resolution and work strike actions at pt swakarya indah busana tanjungpinang. Actions for arrears in wages carried out by PT. Swakrya Indah Busana which cannot afford to pay lasts for three months, especially in July, August and September. This caused employees to go on strike. The use of the method applied in this scientific work is descriptive qualitative method. The results of this research are that the company's inability to pay is in the case of buyers who are in arrears in payment, but the company's responsibility for workers' rights is still being pursued. The company's agreement to pay unpaid wages and remaining allowances so that workers return to work as before.